Operational Risk Assessment and Its Role in Mitigating Damages in Commercial Banks: An Analytical Study of Expert Opinions in the Kurdistan Region - Iraq. (Raparin Journal of Humanities (RJH), 2023)
The aim of this study is to measure and analyze operational risks and identify the most important causes of operational risks in banks in the Kurdistan Region, based on the opinions of experts in this field. Operational risks affect all banking services and operations, such as internal systems, external events and human factors, which can cause significant losses for banks. Therefore, banks need to adopt evolutionary approaches to competition and risk management. To conduct the research, a selection of banks operating in the Kurdistan region was chosen as a case study area to identify the most significant causes of risks in banks.In order to achieve the aim of the study, the Analytic Hierarchy Process (AHP) methodology was used, relying on (SPSS.V.22) software as one of the standard economic methods for analyzing information obtained from a questionnaire administered to selected banks operating in the Kurdistan Region - Iraq.The study found a significant inverse relationship between operational risk assessment and the reduction of harm in commercial banks. This means that the higher the operational risk standards adopted, the lower the likelihood of injury in banks. Additionally, most banks have a plan for identifying and defining operational risks, and that many of the respondents confirmed the presence of operational risk definition and identified in the bank's approved plan for managing operational risks by the board of directors. This indicates that banks recognize the importance of identifying and managing operational risks as part of overall risk management. Data analytics and results should help increase this awareness and improve business risk management processes and procedures.